It equals 2p because p+p=2p.
You can solve this for p:2m + 2p = 162p = 16 - 2mp = 8 - mIf you supply a value for "m", you can then calculate p.You can solve this for p:2m + 2p = 162p = 16 - 2mp = 8 - mIf you supply a value for "m", you can then calculate p.You can solve this for p:2m + 2p = 162p = 16 - 2mp = 8 - mIf you supply a value for "m", you can then calculate p.You can solve this for p:2m + 2p = 162p = 16 - 2mp = 8 - mIf you supply a value for "m", you can then calculate p.
To simplify 2p + 7p, you first combine the like terms by adding the coefficients of the p variable. In this case, 2p + 7p is equal to 9p. Therefore, the simplified form of 2p + 7p is 9p.
In algebra, the expression 2p + 1 represents the sum of twice the value of the variable p and 1. This expression can be simplified by multiplying 2 and p to get 2p, and then adding 1 to get the final result. Therefore, the simplified form of 2p + 1 is 2p + 1.
If it's:p^2 - 2p - 24 =0Then Factorise:p^2 - 2p - 24 = 0(p - 6)(p + 4) = 0Therefore:(p - 6) = 0 OR (p + 4) = 0p = 6 OR p = -4Answer: p = 6 or -4
If -4 = 2p+10 Then the value of p is -7
If: 2p/3 -12 = -2 then the value of p works out as 15
It equals 2p because p+p=2p.
-3+4p-2p=1 -3+2p=1 2p=4 p=2
We can not provide a numerical answer for this question as these (p and x) are variables and their value is not fixed (it varies). We have not been told the value of either variable. However we can simplify this expression.-2p + 4x - 6p = 4x - 8p.We have simply combined the -2p and the -6p, which we can do as 2 of something plus 6 of the same thing will always equal 8 of that thing.-2 + -6 = -8. Therefore -2p + -6p equals -8p and hence the answer above.
You can solve this for p:2m + 2p = 162p = 16 - 2mp = 8 - mIf you supply a value for "m", you can then calculate p.You can solve this for p:2m + 2p = 162p = 16 - 2mp = 8 - mIf you supply a value for "m", you can then calculate p.You can solve this for p:2m + 2p = 162p = 16 - 2mp = 8 - mIf you supply a value for "m", you can then calculate p.You can solve this for p:2m + 2p = 162p = 16 - 2mp = 8 - mIf you supply a value for "m", you can then calculate p.
To find the value of p, simply use addition, subtraction and division to isolate p: 5p -1 = 2p + 20 5p - 2p - 1 = 2p - 2p + 20 3p - 1 + 1 = 20 + 1 3p/3 = 21/3 p = 7 The value of p is 7.
To simplify 2p + 7p, you first combine the like terms by adding the coefficients of the p variable. In this case, 2p + 7p is equal to 9p. Therefore, the simplified form of 2p + 7p is 9p.
That depends what the value of p is.
2p
The number 2p has 4 factors: 1, 2, p, and 2p.
Assuming 2p + y = 0, then 2p = -y p = -y/2